2001
DOI: 10.1152/ajpcell.2001.281.4.c1344
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of AE2 anion exchanger by intracellular pH: critical regions of the NH2-terminal cytoplasmic domain

Abstract: The role of intracellular pH (pH(i)) in regulation of AE2 function in Xenopus oocytes remains unclear. We therefore compared AE2-mediated (36)Cl(-) efflux from Xenopus oocytes during imposed variation of extracellular pH (pH(o)) or variation of pH(i) at constant pH(o). Wild-type AE2-mediated (36)Cl(-) efflux displayed a steep pH(o) vs. activity curve, with pH(o(50)) = 6.91 +/- 0.04. Sequential NH(2)-terminal deletion of amino acid residues in two regions, between amino acids 328 and 347 or between amino acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
134
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(142 citation statements)
references
References 30 publications
8
134
0
Order By: Relevance
“…Full-length cDNAs were cloned into PCR-cloning vector pCRII (Invitrogen), and plasmid cDNA inserts were sequenced in entirety to ensure absence of PCR-introduced mutations, then subcloned into oocyte expression vector pXT7 (13,50) and mammalian expression vector pcDNA3 (Invitrogen). For immunodetection at the oocyte surface, each cDNA in pXT7 was also hemagglutinin (HA)-tagged at its NH 2-terminus through flexible linker sequence GASG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-length cDNAs were cloned into PCR-cloning vector pCRII (Invitrogen), and plasmid cDNA inserts were sequenced in entirety to ensure absence of PCR-introduced mutations, then subcloned into oocyte expression vector pXT7 (13,50) and mammalian expression vector pcDNA3 (Invitrogen). For immunodetection at the oocyte surface, each cDNA in pXT7 was also hemagglutinin (HA)-tagged at its NH 2-terminus through flexible linker sequence GASG.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of oocyte pH i. Oocyte intracellular pH (pHi) was measured using pH microelectrodes as described previously (50). pH electrodes were pulled on a vertical electrode puller (model 730, Kopf Instruments) from borosilicate glass tubing (M1B150F-6, WPI) prewashed with nitric acid and ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…15 and 16), consistent with its proposed role in pH i recovery from alkaline loads. Recombinant AE2 when expressed in tissue culture cells (17, 18) or in Xenopus oocytes (12,13,19) is highly sensitive to changes in both pH o and pH i . Similarly, recombinant cardiac AE3 expressed in Xenopus oocytes is responsive to changes in pH i (19).…”
mentioning
confidence: 99%
“…Recombinant AE2 when expressed in tissue culture cells (17, 18) or in Xenopus oocytes (12,13,19) is highly sensitive to changes in both pH o and pH i . Similarly, recombinant cardiac AE3 expressed in Xenopus oocytes is responsive to changes in pH i (19).Structure-function experiments have indicated that an operationally defined AE2 "pH sensor site" that enhances pH o sensitivity of anion transport is localized to the transmembrane domain (13). This study also demonstrated that the extracellular proton sensitivity (pH o(50) value) of AE2-mediated 36 Cl Ϫ influx (ϳ7.0 under conditions of unclamped pH i ) was acidshifted by up to 0.7 units following various truncations of the cytoplasmic NH 2 -terminal domain.…”
mentioning
confidence: 99%
See 1 more Smart Citation